Analisis Pengaruh Future Value Dan Present Value Terhadap Laba Perusahaan PT. Sumber Alfaria Trijaya Tbk - Muthia Afrilitaa; Dea Saskia Amanda Putri; Cut Amelia; Dimas Januardi; Josep Irwanda Situmorang; Muhammad Ikhsan; Reni Humairah (CV. ITTC INDONESIA, 2025)
The purpose of this study was to analyze the effect of the concepts of Future Value (FV) and Present Value (PV) on the profit of PT Sumber Alfaria Trijaya Tbk (AMRT). The study used a quantitative analysis method with a time value of money approach to evaluate the company's financial performance in the 2020-2025 period. The data used includes the company's annual and quarterly financial statements, with analysis using the mathematical formulas FV and PV for projection and evaluation of investment value. The results showed that FV and PV analysis had a significant influence on the company's profit growth, with the discount rate used influencing Alfamart's investment and retail business expansion decisions.